Influence of surcharge on negative skin friction / Rosamrulanwar Rosdi - Rosdi, Rosamrulanwar (2000)
This project paper presents some laboratory studies of the influence of surcharge on negative skin friction on clay specimen. The objective of this experiment is to study the effect of variable surcharges on negative skin friction and strain energy in the member of the pile. Negative skin friction is the downward force acting on a pile as a result of relative downward displacement between the pile and surrounding soil. The diameter of the pile is 2cm and 3 cm having a length about 91 cm each. The specimens were each lm in diameter and about 1.5 m in height. They were reconstituted from Speswhite Kaolin (a China clay) and consolidated one dimensionally with top and bottom drainage to the required stress history. Two measurements system were used such that strain gages (to measure strain energy on the member of the pile) and transducer (to measure settlement of the specimen). The pile (that has been placed strain gages at interval of 200 mm from each other) was penetrated in the steel-testing chamber to a certain depth and surcharges were applied on the specimen surface and data were collected. In this study, the skin friction of two different types diameter of piles were calculated. The 3 - Method was the most accurate method used to determined the skin fiiction in this study. From the results of both diameters of piles, the skin friction showed that it varies with depth. When the surcharge applied was increased, the skin friction also increased. This phenomenon was transformed to the plotted graph to show the variation of skin friction with depth and loading. From this study, it was found that the highest values of skin friction for both piles were located at the lowest section of the pile while the least value were located at the top of the pile. The highest skin friction value for pile 2cm diameter was 2368.9 kPa and 8170.2 kPa for pile 3cm diameter.